Production of a distilled mango drink: volatile compounds and heavy metal - Giménez-López, Bruno; Quispe, Alejandro; Giménez-Medina, Manuel; Bollet, Herman (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
The optimization of processes for the production of fruit distillates is essential to ensure high product quality, comply with current regulations, and promote the development of the agro-industrial sector. The objective of this study was to evaluate the physicochemical properties of a mango distillate (Mangifera indica L.), varieties Kent and Alphonso, in order to optimize its production process, the fruits underwent controlled fermentation and subsequent distillation, during which volatile compounds and heavy metals were analyzed. The results showed significant differences between both varieties in terms of the concentration of ethyl acetate and furfural, which influence the sensory profile of the distillate. Methanol concentrations and other harmful compounds remained within regulatory limits. However, the copper concentration exceeded the limit allowed by the Peruvian Technical Standard (5 mg.L-1), while zinc levels remained within safe parameters according to the WHO. This study demonstrates that, with adjustments in process control, mango distillate has the potential to be a high sensory quality product suitable for commercialization.